The Holy Spirit and the Church according to the New Testament: Sixth International East-West Symposium of New Testament Scholars, Belgrade, August 25 to 31, 2013 - Karakolēs, Chrēstos K.; Dragutinović, Predrag; Niebuhr, Karl-Wilhelm; Wallace, James Buchanan (Wissenschaftliche Untersuchungen zum Neuen Testament, 2020)
Cover -- Title -- Table of Contents -- Preface -- Karl-Wilhelm Niebuhr - Introduction -- Part One: Biblical Scholarship in Serbia -- Irinej Bulović - The Holy Spirit and the Church. An Orthodox Perspective -- Vladan Tatalović - Orthodox New Testament Scholarship in Serbia -- Part Two: Papers from the Symposium -- N. T. Wright - The Glory Returns: Spirit, Temple and Eschatology in Paul and John -- Christos Karakolis - The Holy Spirit in Luke-Acts: Personal Entity or Impersonal Power? A Synchronic Approach -- Daniel Marguerat - The Work of the Holy Spirit in Luke-Acts: A Western Perspective -- Predrag Dragutinović - The Holy Spirit and the Church in the Gospel of John. A Discourse Analysis of John 20:19-23 -- Andreas Dettwiler - The Holy Spirit in the Gospel of John from a Western Perspective -- John Fotopoulos - The Holy Spirit in Paul from an Orthodox Perspective -- Volker Rabens - The Holy Spirit and Deification in Paul: A 'Western' Perspective -- Demetrios Bathrellos - The Holy Spirit and the New Testament in St. Symeon of Thessalonica (†1429) -- Katharina Bracht - Augustine and His Predecessors Interpreting the New Testament on the Origin of the Holy Spirit. The Question of filioque -- Harald Buchinger - The Holy Spirit and the Church in Liturgy. A "Western Perspective" -- Part Three: Contributions from the Seminars -- The Holy Spirit in Ancient Judaism -- Rodoljub S. Kubat - The Spirit in the Wisdom of Solomon and its Old Testament Background -- James Buchanan Wallace - Spirit(s) in the Testaments of the Twelve Patriarchs -- Carl R. Holladay - Spirit in Philo of Alexandria -- The Holy Spirit and the Church in the Gospels -- Armand Puig i Tàrrech - Holy Spirit and Evil Spirits in the Ministry of Jesus -- Joel Marcus - The Spirit and the Church in the Gospel of Mark -- The Holy Spirit and the Church in Second Century Christian Writings.